Hallazgo de nodulos tiroideos en ecotomografias de adultos asintomaticos - Guerra B., Marcela; Arroyo P., Alejandro; Ortega F. , Ximena; Carrasco T., Raquel (Revista Hospital Clínico Universidad de Chile, 1997)
To determine the prevalence of thyroid nodules in the healthy population, ultrasonography (US) of the thyroid gland was performed in 144 persons (72 women and 72 men), aged 15-72 years with average 35 years, in and urban area of Santiago de Chile where goiter is not considered endemic. Subjects with any previous thyroid were excluded. 59% had normal nutritional state, 15,3o/o were slim and 25,7% were obeses. Thirty thyroid nodules were founded in 21 ( 14,6%) subjects: 15 female and 6 male. Thirteen (9%) subjects had solitary nodules and 8 (5,6%) had multiple nodules. 12 nodules were solid. The mayority of the people with nodules (16 of 21) were subjects of normal weight, 1 nodule was f ounded in slim and 4 in obeses. The results are in accordance with other studies indicating that focal nodular changes of the thyroid gland are common in healthy population and with more frequency in women. Besides the nodules with old age. The frequency of the nodules in our group was less than other studies, because our population was younger.